Anaphylactic Shock During Pediatric Anesthesia: An Unexpected Reaction to Sevoflurane - Simonini, Alessandro; Brogi, Etrusca; Gily, Brunella; Tosca, Mariangela; Barbieri, Claudia; Antonini, Francesca; Del Zotto, Genny (Frontiers in Pediatrics, 2018)
During general anesthesia, while muscle relaxants, latex and antibiotics are normally considered as very common causes of anaphylactic reactions, there are no documented cases of anaphylaxis due to inhalational agents. We report the case of a 6-year-old child scheduled for adenotonsillectomy who had an anaphylactic shock reaction due to Sevoflurane. Several allergic tests were performed to detect the trigger. Drugs used during operation were tested on both patient and three matched controls. While controls were negative, the patient displayed a positive reaction to Sevoflurane To our knowledge, this is the first published report describing an allergic reaction caused by a volatile anesthetic.